Program Evaluation of Group Transcending Self Therapy: An Integrative Modular Cognitive-Behavioral Therapy for Substance Use Disorders. (August 2020) - Polak, Kathryn; Meyer, Brian L; Neale, Zoe E; Reisweber, Jarrod
Objectives: Substance Use Disorders (SUDs) are increasingly prevalent among Veterans. Effective interventions for SUDs that also meet the clinical reality of open treatment groups are needed. Transcending Self Therapy: Group Integrative Cognitive Behavioral Treatment (Group TST-I-CBT) was developed to address this need. Group TST-I-CBT is a four-module, 20-session treatment designed so that a person can enter at any point in the treatment. We conducted a program evaluation of Group TST-I-CBT for veterans with SUDs. Methods: Participants were N = 68 veterans enrolled in the 28-day Substance Abuse Residential Rehabilitation Treatment Program at an urban Veterans Administration Medical Center who received either Group TST-I-CBT (N = 34) or treatment-as-usual (TAU; N = 34). Medical records were reviewed and participant treatment outcome data was retrieved. Group TST-I-CBT clients completed a knowledge and feedback form at treatment completion. Results: Compared to TAU participants, Group TST-I-CBT participants were significantly less likely to have a positive urine drug screen (UDS) during treatment (17.6% versus 0%; P  = .01) and within one month post-discharge (50% versus 17.6%; P  = .04). Among Group TST-I-CBT clients, Quality of Life Inventory scores significantly increased by an average of 14 points from pre- to post-treatment, t (15) = –3.31, P  = .005, d  = 0.83. Group TST-I-CBT clients displayed cognitive-behavioral therapy knowledge (mean correct answers ranged from 92%-100%) and rated Group TST-I-CBT as helpful, understandable, and useful (mean scores ranged from 9.3-9.6 out of 10). Conclusions: These preliminary data indicate that Group TST-I-CBT may be an effective group therapy as part of SUD treatment. A formal randomized controlled trial of Group TST-I-CBT may be warranted.